Optimalizing Regional People’s Representative Council’s Honorary Board’s Duties-Authorities in Upholding Rules and Ethic Codes - Sofwan, Imam; Suparnyo, Suparnyo (Interdisciplinary Social Studies, 2023)
Background: The key to successful regional governance is the DPRD's ability to carry out its functions simultaneously, proportionally and sustainably. In fact, the implementation of DPRD functions does not always run as it should. There is a need for an internal DPRD oversight body to enforce the DPRD's Rules of Procedure and code of ethics. The Ethics Council as one of the permanent apparatuses of the DPRD is expected to be able to guarantee the upholding of the DPRD's rules and code of ethics. Aim: This research focuses on the reasons for the non-optimal implementation of their duties and authorities. Method: This legal research uses a non-doctrinal or empirical juridical approach, the type of data used is primary data, secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials. Methods of data collection using interview techniques and literature study. The collected data was then analyzed qualitatively. Findings: The reason or cause for not optimally carrying out the duties and authorities of the DPRD honorary body in enforcing the DPRD's rules and code of ethics is the existence of internal factors including the tendency to be subjective. There is an opinion within the DPRD that the DPRD's honorary body can act on alleged violations of the rules and regulations.